2012
DOI: 10.1097/sap.0b013e3182749d31
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Applications of the Pedicled Anterolateral Thigh and Vastus Lateralis Myocutaneous Flaps

Abstract: We describe our experience in expanding the use of pedicled anterolateral thigh and vastus lateralis myocutaneous flaps. A total of 33 patients underwent 34 flaps between March 2003 and January 2012. The defects included 18 ischial, 3 trochanteric, 5 lower abdomen, 2 perineogenital, 1 groin, and 5 knee defects. There were 29 proximal pedicled (2 of which were preexpanded), 3 distal pedicled, and 2 propeller flaps. Complications included 1 total necrosis, 1 partial necrosis, 3 wound dehiscence in recipient site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It may be used for small defects as reported in case 2, but may also be used for extensive defects, as in case 1. While its foremost use is as a free flap, its use as a pedicled flap may also be unrivalled; the possibilities presented by pedicle size and length, the size of the flap that can be harvested, and the different components that can be included, as well as the fact that a reverse flap can be raised, make it a favourite reconstructive choice for defects within its area of reach (12,14). Gravvanis et al reported excellent blood flow in reverse ALT flaps they used for the coverage of knee and proximal leg defects (13).…”
Section: Discussionmentioning
confidence: 99%
“…It may be used for small defects as reported in case 2, but may also be used for extensive defects, as in case 1. While its foremost use is as a free flap, its use as a pedicled flap may also be unrivalled; the possibilities presented by pedicle size and length, the size of the flap that can be harvested, and the different components that can be included, as well as the fact that a reverse flap can be raised, make it a favourite reconstructive choice for defects within its area of reach (12,14). Gravvanis et al reported excellent blood flow in reverse ALT flaps they used for the coverage of knee and proximal leg defects (13).…”
Section: Discussionmentioning
confidence: 99%
“…Although the tensor fascia lata (TFL) flap remains the workhorse flap for trochanteric region reconstruction due to its reliability and ease of harvest [2], it has significant shortcomings. In recent years, the pedicled anterolateral thigh (ALT) flap has be-come more popular, and it now has an established role in reconstruction of defects in the perineum, groin, anterior abdominal wall, and thigh [3][4][5][6][7]. However, few case series in the literature have reported utilizing the pedicled ALT flap for trochanteric pressure sore reconstruction [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…come more popular, and it now has an established role in reconstruction of defects in the perineum, groin, anterior abdominal wall, and thigh [3][4][5][6][7]. However, few case series in the literature have reported utilizing the pedicled ALT flap for trochanteric pressure sore reconstruction [8][9][10][11].…”
mentioning
confidence: 99%
“…Song reported ALT flaps based on the blood supply from septocutaneous or musculocutaneous perforators from the lateral femoral circumflex artery or the profundus femoral artery. This flap has the advantages of a wide skin paddle, a long large caliber pedicle, possible simultaneous two-team approach(Hsu et al, 2012;Lee, St- Hilaire, Christy, Wise, & Rodriguez, 2010;LoGiudice et al, 2014). In addition, if the width of the donor site is less than 8 cm, primary closure is possible and the scar can be easily covered due to the nature of its location(Ali, Bluebond-Langner, Rodriguez, & Cheng, 2009).…”
mentioning
confidence: 99%